The Role of Educational Forests in Community Empowerment and Climate Change Mitigation: A Case Study at Tadulako University - Abdul Rosyid; Golar; Budi Setiawan; Rhamdhani Fitrah Baharuddin; Hamka (Jurnal Penelitian Pendidikan IPA, 2025)
Educational Forests are greatly needed by higher education institutions, especially those studying forestry. Various activities can be carried out by students, lecturers, and related parties to be involved in research in order to develop science and knowledge so that they can make real contributions, and empower communities around forest areas to be competitive so that they do not have a high enough value for forest resources, especially wood forest products. In addition, the existence of educational forests is considered capable of mitigating climate change at a micro level. The research was conducted in the Tadulako University Educational Forest as shown in the picture above. The stages of this research consist of two, namely a ground check by taking random samples of trees. Then the second is to identify local community wisdom using qualitative methods with the Rapid Rural Appraisal approach. This research was conducted in the Tadulako University Educational Forest with a direct observation approach. The results of this study found that the land in the forest is still maintained by implementing a forestry system in the form of, where the community utilizes the forest by taking non-timber forest products, rattan, and air ecosystem services.